Collaborative Governance in Smart Branding of Tourism Sector in Banjarmasin City - Ariyani, Erma; Arisanty, Deasy (Journal of Scientific Insights, 2025)
This study aims to analyze the implementation of collaborative governance in the development of smart branding in the tourism sector of Banjarmasin City. The main focus of this study is to identify the patterns of collaboration between the actors involved, as well as to analyze the strategies and innovations applied in an effort to form a city identity based on local potential and digital technology. The research method used is a qualitative approach with data collection through in-depth interviews and observations of various stakeholders such as the Culture Office, Youth Sports and Tourism, the private sector, local communities, and academics. The results show that while there is significant potential to create a strong branding ecosystem, collaboration between government and non-government actors has not been fully optimal. In addition, the application of digital technology in the tourism branding strategy of Banjarmasin City is still limited, while the contribution of the local community in the co-creation branding process has not been properly facilitated. This study also found that low coordination between government agencies and a lack of data-based evaluation are obstacles to the effectiveness and sustainability of city branding strategies. Based on the findings, this study recommends the establishment of a more inclusive cross-sectoral collaboration forum, digital capacity building in tourism promotion, and policy updates that support the integration of data-based branding strategies and technology